Diagnostics with clinical microbiome‐based identification of microorganisms in patients with brain abscesses—a prospective cohort study. Issue 11 (13th October 2021) - Hansen, Katrine Hartung; Justesen, Ulrik Stenz; Kelsen, Jesper; Møller, Kirsten; Helweg‐Larsen, Jannik; Fuursted, Kurt
Abstract : Brain abscesses are often polymicrobial and of unclear primary origin. Here, we compare the use of next‐generation sequencing (NGS) technology with classical microbiological diagnostics for identification of clinically relevant microorganisms and describe the microbiome profiling with respect to the primary source of brain abscess. Thirty‐six samples from 36 patients, with primary brain abscesses, were subjected to both culture‐ and 16S/18S rRNA Sanger sequencing‐based diagnostics ("standard methods") and compared to a 16S/18S amplicon‐based NGS, which were also subjected to a microbiome diversity analyses. Forty‐seven species were identified with "standard methods" compared to 96 species with NGS, both confirming and adding to the number of species identified (p < 0.05). The variation of the brain abscess microbiome diversity was not continuous but could be stratified comparing the presumable origin of infection ("dental, " "sinus, " "disseminated, " or "unknown"). Alpha diversity did not differ (p > 0.05) between groups while beta diversity differed significantly (p = 0.003) comparing disseminated vs the other presumable origin of infection. Interesting, clustering was also detected between "dental" and "sinusitis, " although not significantly (p = 0.07). Microbiome‐based diagnostics can increase sensitivity without losing specificity. The bacterial beta diversity differed between the presumably origin of the brain abscess and might help to clarify the primary source of infection.